Trip Report on RiceAdvice Lite validation trial (RAL VAT) protocol activities in framework of AICCRA project to Syngenta - Ahouanton, Kokou (2024)
This report outlines the activities and outcomes of the RiceAdvice Lite validation training conducted in Mali from May 24 to June 16, 2024, under the AICCRA project. The training aimed to equip partners from the Syngenta Foundation and the Institut d'Économie Rurale (IER) with the skills necessary to implement and manage the RiceAdvice Lite protocol for the 2024 wet season. Sessions were held across Sikasso and Segou, focusing on setting up trial plots, data collection, and application use. Over 100 rice farmers' fields were prepared for trials, ensuring readiness for effective data-driven agricultural practices.